A multiple handover method by using the guide of mobile node - Radhwan Mohamed Abdullah; Radhwan Basher; Ayad Hussain Abdulqader (Institute of Advanced Engineering and Science, 2021)
Today’s healthcare system can be characterised using the up-and-coming integral component of mobility management of wireless body area networks (WBANs). In general, remote sensor nodes of WBAN are positioned on the body of a subject. Meanwhile, recommendations for specific proxy mobile IPv6 (PMIP) approaches have emerged, but its comparatively unfeasible nature in terms of group mobility management with regards to WBAN. Therefore, it shows a likelihood for expansive registration and handover interruptions. Thus, this work offered an alternative aimed at curbing such restrictions via an enhanced group mobility management method. The approach underlined the integration of authentication, authorisation, and accounting (AAA) services into the local mobility anchor (LMA) as another option for independent practice. Moreover, the proxy binding update (PBU) and AAA inquiry messages were consolidated, whereas the AAA response and proxy binding acknowledge (PBA) message were amalgamated. The resulting outcomes depicted the proposed method’s superior performance in comparison with the current PMIP approaches in the context of registration delay time, handover interruption, and average signalling cost.